Public Policies for the Disposal of Household Waste: The Case of the Municipality of São Borja (Interdisciplinary Studies Journal, 2021)
Household solid waste is a matter of extreme concern and seriousness throughout Brazil. The general objective of this study was to understand the current disposal of household solid waste in the municipality of São Borja/RS, specifically aiming to contribute to public awareness by exposing the importance of proper waste disposal and the consequences of improper disposal for the environment in São Borja. Based on bibliographic research and current legislation, it was found that although there are federal, state, and municipal laws, norms, and decrees emphasizing the importance of environmental education as a tool for raising awareness, their applicability is lacking, as demonstrated by the systematized observations. The study analyzed the waste collection process in the municipality’s streets and the location where waste is stored before being sent to the municipality of Giruá/RS. Therefore, a partnership proposal was made to the Municipal Education Department of São Borja for the implementation of an extension program and the 1st Environmental Seminar of São Borja, specifically targeted at teachers and administrators in the municipal education network, with technical and informative content, a Continuing Education course for municipal school teachers with pedagogical lectures and workshops, educational lectures on waste separation, disposal, and environmentally correct final disposal for all students enrolled in the 11 Municipal Elementary Schools in the urban area, and the implementation of interactive storytelling and play activities for students in the 11 Municipal Early Childhood Education Schools, aiming to raise awareness from early childhood. With the execution of the proposed activities, the objectives of raising awareness within the school community were achieved, as evidenced by the participation and engagement of students, teachers, and managers from the Municipal Education Department and the Agriculture and Environment Department. Formally, evaluation forms were distributed to all participating schools, later submitted to the pedagogical department of the Municipal Education Department for assessment, considering feedback and suggestions for future initiatives.
Keywords: Public Policies; Solid Waste; São Borja; Awareness